Divergência genética em Psidium e estudos de herança e associação genómica da resistência a Meloidogyne enterolobii em híbrido de Psidium com base em polimorfismo de nucleotídeo único - Costa, Soniane Rodrigues da (2017)
The decline of guava is a complex disease, which causes progressive galls in guava roots parasitized by Meloidogyne enterolobii. The objective of the present study is to study the genetic divergence in guava and araçazeiros accessions by means of SNPs markers developed for Eucalyptus to serve as a subsidy for activities of genetic resources and improvement of guava, such as the broad genomic association and to estimate the number of genes involved in resistance to M. enterolobii, using F2 population of Psidium guajava and P. guineense hybrid.In the evaluation of the genetic diversity of Psidium accessions, presented in chapter I, the transferability of Eucalyptus SNPs to Psidium for application in analyzes of genetic divergence and other applications, including studies of genome association. The segregation results and broad sense heritability estimates in population F2, presented in chapter II, support dominance model controlled by two genes, with epistatic effects, and the presence of only one dominant allele conditions the resistance of the hybrid of P. guajava x P. guineense for M. enterolobii. New hybrids of P. guajava with other accessions of wild Psidium should be developed and evaluated in order to increase the sources of resistance to the pathogen, allowing effective control of the same in commercial areas of guava. Seven markers associated with resistance to Meloidogyne enterolobii in Psidium species presented in Chapter III were identified.The results also suggest the existence of different sources of resistance to the nematode, since several SNPs were identified on chromosome 3 of Eucalyptus.